2009
DOI: 10.1089/hum.2008.013
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Characteristics Induced by Linear Polyethyleneimine–Plasmid DNA Complexes in Cultured Macrophages

Abstract: Intravenously injected plasmid DNA (pDNA) complexed with cationic liposome (lipoplexes) caused NF-kappaB-mediated cytokine production from macrophages, induced by CpG sequence in the pDNA. We have reported that cytokine production caused by linear polyethyleneimine (PEI)-pDNA complexes (PEI polyplexes) was much lower than that caused by lipoplexes (Kawakami, S., Ito, Y., Charoensit, P., Yamashita, F., and Hashida, M. [2006]. J. Pharmacol. Exp. Ther. 317, 1382-1390). As Toll-like receptor-9 recognizing CpG sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In our model, PEI alone or PEI/DNA polyplexes could not effectively induce cytokines secretion (Fig. 6a and c) and this is consistent with previous reports and related to its lower induction of NF-kB activation [40]. The homopolymer PDMAEMA also induced high level of cytokines production (Fig.…”
Section: Peg-b-pdmaema Induced Cytokine Production By Murine Macrophagessupporting
confidence: 92%
“…In our model, PEI alone or PEI/DNA polyplexes could not effectively induce cytokines secretion (Fig. 6a and c) and this is consistent with previous reports and related to its lower induction of NF-kB activation [40]. The homopolymer PDMAEMA also induced high level of cytokines production (Fig.…”
Section: Peg-b-pdmaema Induced Cytokine Production By Murine Macrophagessupporting
confidence: 92%
“…A complexing agent that allows endocytosed RNA to exit the endosome and enter the cytoplasm before acidification and TLR signaling would result in reduced TNF-α secretion, as was observed with TransIT-complexed mRNA. In a comparison of cationic liposomes to linear polyethyleneimine (PEI) (a cationic polymer) delivery of CpG containing DNA, it was found that PEI-DNA induced less TNF-α, which was associated with a faster exit from endosomes, while cationic lipid delivery resulted in DNA remaining in vesicular structures for extended periods of time and high levels of TNF-α (30). We similarly observed that cationic liposome complexed RNA induced higher levels of TNF-α compared to the cationic polymer with lipid TransIT.…”
Section: Discussionmentioning
confidence: 99%
“…Among these mesoporous silica nanoparticles, polymers, dendrimers and cyclodextrins represent interesting alternative under active investigation [41]. Among synthetic polymers, polyethylenimine (PEI) is widely used due to its strong proton sponge effect that increases the endosomal escape of siRNA, a phenomenon useful to prevent the toll-like receptor-mediated immunological response that starts in endosome of macrophages [68]. However, synthetic polymer-based delivery systems, such as PEI, can cause toxicity because they are poorly degradable.…”
Section: Synthetic Vector Mediated Delivery Of Sirnamentioning
confidence: 99%